Fermentation and Microencapsulation of Red Palm Oil as a Nutraceutical Source - Nuralang; Ananda, Hertanti Dwi; Nelson; Susanto, Nindita Clourisa Amaris; Tarigan, Indra Lasmana (HAYATI Journal of Biosciences, 2025)
Red palm oil (RPO) has various bioactive and nutritional components with high potential to be developed as a source of nutraceuticals in addition to its potential as a functional food. The fermentation technology is a processing process that affects metabolite activity, increasing the durability of a product. Staphylococcus epidermidis is one of the bacteria that is generally used in the sugar and oil fermentation process. RPO fermentation by Staphylococcus epidermidis is supposed to increase nutraceutical value by adding probiotic properties to RPO products. Moreover, the instability of bioactive compounds in RPO needs to be protected with coating technology microencapsulation. So, this study aims to formulate a microencapsulation procedure for fermented RPO using Staphylococcus epidermidis ATCC 12228 as a potential nutraceutical. RPO was fermented using S. epidermidis with three variations of MRS media and RPO comparison, then microencapsulated using emulsification and extrusion methods. The physicochemical properties and bioactivity of the product, microcapsule, were then analyzed. Our data shows that RPO fermentation was able to increase the chemical components. RPO fermentation produced more 1,2-Benzenedicarboxylic acid (2-Ethylhexyl) ester. Furthermore, microencapsulation of fermented RPO has better yield, efficiency, and solubility in water than non-fermented RPO microencapsulation. Moreover, our work also shows that the microencapsulation process increased RPO stability.